Behavioural response of the woodwasp Sirex noctilio to volatile emissions of its fungal symbiont - Fernández Ajo, A. A. (2015)
The wood-boring wasp, Sirex noctilio, is a global invasive pest that infectsand kills pine trees by inoculating spores of a symbiotic fungus (Amylostere-um areolatum) at oviposition. Wasp larvae depend on fungal growth tofeed, while the fungus relies on female wasps to initially condition thepine tree by inoculating a phytotoxic venom and for dispersal. Wasp lar-vae use the fungus as an external gut for the digestion of lignocellulosiccompounds resulting in a strong correlation between fungal growth insidethe wood and wasp ﬁtness. This study explores the hypothesis that femalewasps will use fungal volatiles as a synomone in the process of locatingsuitable oviposition areas (i.e. trees). Using a Y-tube olfactometer, adultfemale wasp behaviour was assessed towards fungal and pine tree volatiles(i.e. positive control). Our results are the ﬁrst to demonstrate attraction offemale S. noctilio towards volatiles of their fungal symbiont. Furthermore,the positive response towards these volatiles seems to be stronger than theresponse to a known attractant (i.e. pine volatiles). These results could bean important contribution to improving baits for monitoring and controlpurposes. Further work is needed, mainly oriented towards the identiﬁca-tion of the volatiles that trigger the observed attraction response and theirpossible synergistic effects with tree volatiles.